FEATURES OF EXAMINATION AND INTERVENTION OF CHILDREN WITH CONGENITAL MUSCULAR TORCEMIA WITHIN THE FRAMEWORK OF PHYSICAL THERAPY - Лістау, Карина; Толок, Віктор (SWorldJournal, 2025)
Congenital muscular torticollis (CMT) is a persistent disorder in infants, usually diagnosed at birth or shortly thereafter, characterized by a pathological tilt of the head towards the shortened sternocleidomastoid, sometimes trapezius muscle, and limite